The Implementation of Deliberation as a Form of Collective Decision in Islamic Law - Wahid, Sahid; Yusuf, Muhammad; Mardan, Mardan (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
Deliberation is one of the main principles in Islamic teachings that functions as a means to achieve fair and wise collective decisions. In Islamic law, deliberation plays an important role in the decision-making process, both in the political, social, and legal realms. This study aims to examine in depth the concept of deliberation based on the arguments of the Qur'an and Hadith, and its application in the formation of Islamic law (sharia). Through a normative approach and analysis of classical and contemporary literature, this study highlights the importance of deliberation as a mechanism to ensure the participation of the people in the legislative process. In addition, this study also explores how collective decisions taken through deliberation are able to reflect justice, equality, and mutual agreement, in accordance with Islamic values. The findings of this study indicate that deliberation is not only relevant in the context of traditional Islamic law, but also has strong significance in modern legal and governance systems, especially in efforts to promote transparency and accountability.